The body in Tolkien's legendarium essays on Middle-earth corporeality - Vaccaro, Christopher (McFarland & Co., Inc., Publishers, 2013)
"The timely collection of essays is thematically unified around the subject of corporeality. Its theoretical underpinnings emerge out of feminist, foucauldian, patristic and queer hermeneutics. While Tolkien's The Lord of the Rings is central to most analyses, authors also cover The Hobbit, The Silmarillion, and material in The History of Middle-earth"--